Deletion of the murine ortholog of human 9p21.3 locus promotes atherosclerosis by increasing macrophage proinflammatory activity - Kettunen, Sanna; Ruotsalainen, Anna-Kaisa; Örd, Tiit; Suoranta, Tuisku; Heikkilä, Janne; Kaikkonen, Minna U.; Laham-Karam, Nihay; Ylä-Herttuala, Seppo (Frontiers in Cardiovascular Medicine, 2023)
Background Several genome-wide association studies have reported a risk locus for coronary artery disease (CAD) in the 9p21. 3 chromosomal region. This region encodes a lncRNA in the INK4 locus (ANRIL) and its genetic variance has a strong association with CAD, but its mechanisms in atherogenesis remain unclear. Objectives This study aimed to investigate the role of the murine ortholog of human 9p21.3 locus in atherogenesis in hypercholesterolemic mice. Methods Murine 9p21.3 ortholog knockout mice (Chr4Δ70kb/Δ70kb) were crossbred with Ldlr−/−ApoB100/100 mice, and atherosclerotic plaque size and morphology were analyzed on a standard or a high-fat diet (HFD). The hematopoietic cell-specific effect of Chr4Δ70kb/Δ70kb on atherosclerotic plaque development was studied via bone marrow (BM) transplantation, where Chr4Δ70kb/Δ70kb or wild-type BM was transplanted into Ldlr−/−ApoB100/100 mice. The role of Chr4Δ70kb/Δ70kb in macrophage M1/M2 polarization was studied. In addition, single-cell sequencing data from human and mouse atheroma were analyzed to show the expression profiles of ANRIL and its murine equivalent, Ak148321, in the plaques. Results Both systemic and hematopoietic Chr4Δ70kb/Δ70kb increased atherosclerosis in Ldlr−/−ApoB100/100 mice after 12 weeks of HFD. The systemic Chr4Δ70kb/Δ70kb also elevated the number of circulating leukocytes. Chr4Δ70kb/Δ70kb BMDMs showed enhanced M1 polarization in vitro. Single-cell sequencing data from human and mouse atheroma revealed that ANRIL and Ak148321 were mainly expressed in the immune cells. Conclusion These data demonstrate that both systemic and BM-specific deletion of the murine 9p21.3 risk locus ortholog promotes atherosclerosis and regulates macrophage pro-inflammatory activity, suggesting the inflammation-driven mechanisms of the risk locus on atherogenesis.